(untitled) - Styring, James (Oxford, 2010)
These motivating non-fiction readers are rich in content and beautifully illustrated. Fascinating information in carefully graded language appeals to a broad range of students and supports English across the curriculum, making the series perfect for CLIL (Content and Language Integrated Learning).
Keywords: Tiếng Anh,Phương tiện vận chuyển,Transportation,English language; Đọc hiểu,Văn học thiếu niên,Juvenile literature,Reading comprehension